The relationship between miRNA biogenesis and RNA splicing - Parsons, Aimee (2018)
MiRNAs (miRNAs) are important for the proper regulation of translation, with aberrant miRNA expression contributing to diseases such as cancer. MiRNAs are expressed from longer primary-miRNA transcripts and found in a variety of genomic locations, including introns and exons of coding or long noncoding RNAs. MiRNA biogenesis begins with excision of the precursor miRNA hairpin by the Microprocessor complex which consists of two proteins: Drosha and DGCR8. Both Microprocessor cleavage and splicing occur co-transcriptionally.